Painting in excess : Kyiv's art revival, 1985-1993 - Martynyuk, Olena; Bazdyrieva, Asia.; Lozhkina, Alisa; Solovĭov, Oleksandr; Jane Voorhees Zimmerli Art Museum (New Brunswick, NJ : Zimmerli Art Museum, Rutgers University Press, 2021)
The upheavals of glasnost and perestroika followed by the collapse of the Soviet Union remarkably transformed the art scene in Kyiv, launching Ukrainian contemporary art as a global phenomenon. The previously calm waters of the culturally provincial capital of the Ukrainian Soviet Republic became radically stirred with new and daring art made publicly visible for the first time since the avant-garde period of the early twentieth century. As artists were freed from the dictates of the fading Communist ideology and the constraints of late socialist realism, an explosion of styles emerged, creating an effect of baroque excess. This exhibition catalogue traces and documents the diverse artistic manifestations of these transitional and exhilarating years in Kyiv while providing some historical artworks for context. Published in partnership with the Zimmerli Museum.
Frontmatter -- Contents -- Foreword -- Acknowledgments -- Introduction -- 1. Painting Ukrainian Perestroika: A Parade of Excesses -- 2. The Point of No Return: The Art of Kyiv at a Historical Crossroads -- 3 Back and Down to Empty Landscapes: Notes on Ukraine's Reverse Modernism -- 4. Prodigal Children of Socialist Realism: New Ukrainian Art and the Soviet Art School -- 5. Collecting Eras: A Conversation -- Artists' Statements -- Plates -- Selected Bibliography -- Catalogue of the Exhibition -- Index of Artists in the Exhibition -- Contributors
Includes bibliographical references and index.
This book accompanies the exhibition "Painting in Excess: Kyiv's Art Revival, 1985-1993" organized by the Zimmerli Art Museum, Rutgers, The State University of New Jersey
Online resource; title from digital title page (viewed on August 11, 2022).
JSTOR
Keywords: Painting -- Ukraine -- Kyïv -- 20th century -- Exhibitions; Art -- Ukraine -- Kyïv -- 20th century -- Exhibitions; Art, Ukrainian -- 20th century -- Exhibitions; Kyïv (Ukraine); Peinture -- Ukraine -- Kiev -- 20e siècle -- Expositions; Art ukrainien -- 20e siècle -- Expositions; Art -- Ukraine -- Kiev -- 20e siècle -- Expositions; ART / General; Painting; Art; Art, Ukrainian; Ukraine -- Kyïv; 1900-1999; Kyiv, USSR, Soviet Union, Ukraine, glasnost, perestroika, collapse of the Soviet Union, avant-garde, art, artists, Ukrainian Soviet Republic, twentieth century, 20th century, realism, socialist realism, communism, artistic expression, reverse modernism, history, Iron Curtain, Cold War, Russia; exhibition catalogs; Exhibition catalogs; Exhibition catalogs; Catalogues d'exposition.